The m6A reader YTHDF1 promotes ovarian cancer progression via augmenting EIF3C translation. Issue 7 (30th January 2020) - Liu, Tao; Wei, Qinglv; Jin, Jing; Luo, Qingya; Liu, Yi; Yang, Yu; Cheng, Chunming; Li, Lanfang; Pi, Jingnan; Si, Yanmin; Xiao, Hualiang; Li, Li; et al.
Abstract: N 6 -Methyladenosine (m 6 A) is the most abundant RNA modification in mammal mRNAs and increasing evidence suggests the key roles of m 6 A in human tumorigenesis. However, whether m 6 A, especially its 'reader' YTHDF1, targets a gene involving in protein translation and thus affects overall protein production in cancer cells is largely unexplored. Here, using multi-omics analysis for ovarian cancer, we identified a novel mechanism involving EIF3C, a subunit of the protein translation initiation factor EIF3, as the direct target of the YTHDF1. YTHDF1 augments the translation of EIF3C in an m 6 A-dependent manner by binding to m 6 A-modified EIF3C mRNA and concomitantly promotes the overall translational output, thereby facilitating tumorigenesis and metastasis of ovarian cancer. YTHDF1 is frequently amplified in ovarian cancer and up-regulation of YTHDF1 is associated with the adverse prognosis of ovarian cancer patients. Furthermore, the protein but not the RNA abundance of EIF3C is increased in ovarian cancer and positively correlates with the protein expression of YTHDF1 in ovarian cancer patients, suggesting modification of EIF3C mRNA is more relevant to its role in cancer. Collectively, we identify the novel YTHDF1-EIF3C axis critical for ovarian cancer progression which can serve as a target to develop therapeutics for cancer treatment.